Tax Management Analysis of VAT and Its Implications for the Liquidity of Construction Companies - Cempaka Effendi Gunawan; Arifin Rosid (E-Jurnal Akuntansi, 2025)
The construction sector ranks as the fifth-largest contributor to Value Added Tax )VAT) revenue in Indoneisa. In 2023, total tax revenue realization rached 102.80%, with VAT and Sales Tax on Luxury Good (STLG) contributing 40.9%, highlighting the sector’s strategic role in achieving tax targets. This study aims to evaluate the effectiveness of VAT-related tax management and cash flow management in construction company that has been designated as a taxable entrepreneur (PKP). A case study approach was employed using primary data from interviews with the company’s finance and tax divisions as well as external tax consultants, supported by internal documents and financial statements as secondary data. The findings reveasl that both tax and xash management are ineffective due to the absence of formal tax planning, specifics SOPs, and cash flow challenges caused by delayed client payments. The study recommends establishing a separate tax function, implementing tax-specific SOPs and internal audits, and intergrating financial tax and systems.